SAT0301 A comparative analysis of PSA spondylitis patients with PSA and AS 12 months after initiation of TNFI therapy. (23rd January 2014) - Madruga Dias, J.; Balogh, E.; Harty, L.; Flynn, E.; Grier, A.; Molloy, M.; Minnock, P.; Molloy, E.; Fitzgerald, O.; Veale, D.J.
Abstract : Background: Spondyloarthropathies (SpA) are a family of disorders with common characteristics. This study compares baseline data and clinical outcomes 12 months post-TNFi therapy in patients with PsA plus spondylitis (PsAs), psoriatic arthritis without spondylitis (PsA) and ankylosing spondylitis (AS). Methods: 77 SpA patients (n=23, PsAs; n=26, PsA; n=28, AS) were recruited, prior to TNFi therapy, and followed prospectively for 12 months. PsA was defined by the CASPAR criteria, PsAs plus inflammatory back pain and AS by the ASAS criteria. Demographic, radiographic, clinical and serological data were collected. Kruskal Wallis and Mann Whitney U tests were used to compare non parametric data between categories. Spearman's Rho was used to test significance of correlations between baseline statistics and longitudinal outcomes. Results are presented as the mean and/or percentages. Statistical analysis was performed using SPSS 18. Results: The PsAs group were significantly younger than the AS and the PsA group (43yrs<47yrs<53yrs; p=0.021). PsAs were more frequently male than AS and PsA (65% v 61% v 54%). 79% of AS patients were using NSAIDs compared to 52% of PsAs and 13% PsA. 64% PsAs patients were on Etanercept, 23% on Adalimumab, 9% on Infliximab and 4% Golimumab. PsAs patients had significantly higher DAS28 scores at baseline (5.2 v 4.1, p=0.006) yet lower 1yr DAS28 scores (1.5 v 2.6, p=0.003) compared to PsA. The ESR (2 v 16 v 13, p<0.01) and CRP (3 v 7 v 6, p=0.03) were significantly lower in PsAs compared to both AS and PsA pt's at 1yr, respectively. Conclusions: The PsAs group appear to be younger, more males and have higher DAS28 scores at baseline compared to PsA without spondylitis or AS patients. Disclosure of Interest: None Declared